Shattering the Myth of Costless Price Changes: Emerging Perspectives on Dynamic Pricing - Mark Bergen; Shantanu Dutta; Daniel Levy; Mark Ritson; Mark Zbaracki (Bar-Ilan University, Department of Economics, 2003)
In this paper we argue that pricing is all about price changes, and that the costs of price changes are often simultaneously subtle and substantial. We discuss a framework to deal with the dynamics of changing prices. This framework incorporates customer interpretations of price changes, an awareness of the organizational costs of price changes, investments in future pricing processes, and an understanding of the role that supply chains play in price change strategy. The framework can be used at the tactical level to improve the specific price changes chosen and made, at the managerial level to decide whether or not to make a particular price change at all, and at the strategic level to determine what price adjustment processes should be invested in to improve pricing effectiveness in the future.
Keywords: M31; M10; M20; L11; L16; E31; D40; D20; 330; Pricing; price setting; price adjustment; cost of price adjustment; price change management; investment in pricing processes; supply chains; customer costs of price adjustment